Ecosystem Services Provided by Grass-legume Pastures - Jose C. B. Dubeux; Lynn E. Sollenberger; Mark Mauldin; Liza Garcia (EDIS)
Ecosystem Services are the benefits society obtains from ecosystems. These services benefit both people and the environment. Ecosystem services (ES) provided by grasslands include not only products such as beef and milk (provisioning services), but also biological N2-fixation (BNF) and nutrient cycling (supporting ES), carbon sequestration and greenhouse gas mitigation, water catchment and purification, shade, windbreaks, habitat for pollinators and wildlife (regulating ES), and finally cultural (e.g., hunting, bird watching) and aesthetical ES. Grassland managers are providing these benefits to the entire society and they should receive compensation. Payment mechanisms can work numerous ways, including tax breaks, direct monetary compensation, and cost-share programs. The first step, however, is to measure and put a monetary value on these ES.